(untitled) (The Journal of Psychology and Sociology, 2019)
The present article provides the results of sociological studies, which were performed using questionnaire (quota-area sample). Based on the analysis, were made conclusions about elastic duality and synthetic character of modern youth associations of Kazakhstan, combining the dominant traditional- paternalistic and innovative-democratic attitudes and practices. It was noted that the focus of (according to the majority of respondents) on the involvement of youth in political life of the society, many associations solve the social problems, but not young people. At the same time, the majority of modern youth of Kazakhstan now considers the need of young people in public youth associations has always been a priority. This means the relevance and importance of modern youth associations in a difficult period of social transformation, when young people need the support of society, in solving social problems, in helping to fulfill their ambitions, develop their personal strengths, reach a cultural and spiritual improve- ment, and also to influence social processes. Simultaneously, it shows that Kazakhstan’s youth has a significant potential of social activism.